Letter from Edwin Lonsdale to Margaret M. Booth - Lonsdale, Edwin (1888)
Edwin Lonsdale, a florist, forwards a request to Margaret M. Booth, wife of James Curtis Booth (1810-1888), for information concerning the date of Booth's election to the Horticultural Society for his successor as Secretary, D.D.L. Farson.
Keywords: Booth, James Curtis, 1810-1888; Farson, Daniel D.L; Pennsylvania Horticultural Society